2014
DOI: 10.1039/c4ra08305a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ultrafast excited state dynamics of 2,2′,4,4′,6,6′-hexanitrostilbene using femtosecond transient absorption spectroscopy

Abstract: A study on the dynamics and structures of the excited states of 2,2′,4,4′,6,6′-hexanitrostilbene shows equilibrium between vibrationally hot S1 (S*1) and S1 states with lifetimes of 0.8 and 6 ps, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In addition, 0.59 ps lifetime of S 2 → S 1 was reported for a benzophenone derivative (p-iodobenzophenone) in acetonitrile media 37 . Longer relaxation time with 0.8 ps lifetime was observed from the femto-TA transient absorption spectrum of HNS for its S 2 → S 1 decay in acetontrile media 28 . The ab initio MD study on the uracil in solution 42 , which exhibited good consistency with the experimental observations, also found that 50% of the excited trajectories are still trapped in S 2 after 1 ps, indicating that the depopulation of the S 2 state slowly occur due to internal conversion to the S 1 .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In addition, 0.59 ps lifetime of S 2 → S 1 was reported for a benzophenone derivative (p-iodobenzophenone) in acetonitrile media 37 . Longer relaxation time with 0.8 ps lifetime was observed from the femto-TA transient absorption spectrum of HNS for its S 2 → S 1 decay in acetontrile media 28 . The ab initio MD study on the uracil in solution 42 , which exhibited good consistency with the experimental observations, also found that 50% of the excited trajectories are still trapped in S 2 after 1 ps, indicating that the depopulation of the S 2 state slowly occur due to internal conversion to the S 1 .…”
Section: Resultsmentioning
confidence: 91%
“…Figure 2 shows 2D plot of the spectrum, which covers the range from 400 nm to 710 nm and possess a long delay time of 400 ps. The negative signals (blue region) in the 400–460 nm range should correspond to the ground state bleaching (GSB) or stimulated emission (SE) 28 41 . The positive signals in the region of 460–710 nm should involve in excited state absorption mixed with the simulated emission from the high vibration excited states to the low ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…have been observed [2, 18−21]. The evolution of excited state of HNS has also been observed by the ultrafast absorption experiments [22]. The thermal decomposition of HNS has been analyzed by Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) [20].…”
Section: Introductionmentioning
confidence: 99%